Pembacaan Yasinan dan Al-Barzanji dalam Tradisi Masyarakat Desa Pandan Wangi Kecamatan Jerowaru - Abd Quddus Al Badani; Nurmayanti Nurmayanti (PALAPA, 2024)
Religious traditions are an integral part of rural community life and play an important role in preserving Islamic culture, including in Pandan Wangi Village. This study aimed to describe and analyze the implementation of Yasinan and Al-Barzanji recitations within the religious traditions of the Pandan Wangi Village community. The study employed a descriptive qualitative method with an ethnographic approach through direct observation, in-depth interviews, and documentary study. The findings show that Yasinan and Al-Barzanji recitations function not only as religious rituals but also as a medium of social cohesion, a means of moral education, and an instrument for preserving Islamic cultural values. This tradition is carried out regularly in various events, such as the commemoration of the Prophet’s Mawlid, tahlilan, and other religious activities, and it continues to be maintained amid the challenges of modernization as a collective identity and spiritual heritage transmitted across generations. This study affirms the importance of preserving local traditions as a form of cultural resilience and strengthening religious values in rural community life.